Role of salt concentration lithium perchlorate on ionic conductivity and structural of (glycidyl methacrylate -co-ethyl methacrylate) (70/30) based on a solid polymer electrolyte - Imperiyka M.; Ahmad A.; Hanifah S.A.; Rahman M.Y.A. (2023)
A new solid polymer electrolytes (SPE) comprising copolymer of poly(glycidyl methacrylate, GMA) and (ethyl methacrylate, EMA) as polymer host and LiClO4 as dopant was prepared by solution-casting technique. The copolymer was prepared by photopolymerization method and was characterized using NMR. The SPEs were characterized using electrochemical impedance spectroscopy (EIS), fourier transforms infrared (FTIR) and X-ray diffraction (XRD). The highest conductivity achieved was 4.0x10-4 at 373K with highest conductivity at room temperature (2.7x10-5 S cm-1 at 30 wt. % of LiClO4). The active coordination site for the cation (Li+), three electrons donating functional carbonyl, ether and epoxy group of the GMA-co-EMA host have been evaluated base on their properties that were recorded in (FTIR). The structural analysis showed reduction in copolymer crystallinity phases at its highest conductivity. (2013) Trans Tech Publications, Switzerland.